MENINGKATKAN HASIL BELAJAR IPA MELALUI PENERAPAN METODE CERAMAH PLUS DEMONSTRASI DENGAN MATERI BAGIAN-BAGIAN TUBUH DI KELAS I SD NEGERI 5 BIES KABUPATEN ACEH TENGAH T.P 2013/2014 - Darmiati Darmiati (JURNAL TEMATIK, 2014)
Improving Learning Outcomes Of Sciences By Application Learning Methods Lecture Plus Demonstration With Parts Of The Body In The Class I SD State 5 Bies District Central Aceh Lessons Of Year 2013/2014. The purpose of this study was to obtain a factual overview of the use of lectures plus demonstrations of learning methods can improve science learning outcomes of students in public primary schools 5 Class I Bies Central Aceh district lessons of year 2013/2014. This study uses action research (action research) for three cycles. Each round consists of four phases: design, action and observation, reflection and refisi. The target of this research is the first grade students of SD Negeri 5 Bies Central Aceh district in Aceh province, amounting to 25 samples. Lessons of year 2013/2014 the data obtained in the form of test results, observation sheet teaching and learning activities. Based on these results it can be concluded that learning by teaching learning methods lectures plus demonstrations have a positive impact in improving student achievement is marked by an increase in mastery learning students in each cycle, the first cycle (64.00%), second cycle (76.00 %), the third cycle (88.00%). The application of learning methods lectures plus demonstrations of learning has a positive effect, which can improve student learning outcomes to study the course material received during this time, where it is shown by the average attitude of students who stated that students interested in learning and interested in learning methods lectures plus demonstrations so that they become motivated to learn.